Memilih Circle dalam Perspektif Hadis : Panduan Praktis untuk Menjalani Kehidupan Berlandaskan Ajaran Agama - Rifki Irawan; Muhammad Alif (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
This study examines social ecology from the perspective of hadith science (‘ulum al-hadith), with the aim of exploring the environmental and social values contained in prophetic hadiths. The main focus of this study is the methodological analysis of hadiths related to ecological issues, such as environmental conservation, social justice, and natural resource management. This study uses a hadith criticism approach, namely by examining aspects of authenticity through analysis of sanad (chain of narrators), criticism of matan (the content of the hadith), and contextual and semantic interpretation of hadiths relevant to environmental themes. In this study, the hadiths analyzed were selectively selected based on their relevance to the principles of Islamic social ecology. The analysis process was carried out thoroughly to assess the validity of the hadith and understand its meaning and normative objectives. This approach integrates classical evaluation methods of hadith science with a contemporary ethical perspective, resulting in a comprehensive framework for formulating hadith-based environmental ethics. Research findings indicate that many authentic hadiths contain strong social ecological principles, such as the concept of caliphate (human leadership over the earth), mizan (balance), and distributive justice. These values emphasize the importance of human responsibility in preserving nature and creating harmony between humans and their environment. These hadiths also demonstrate the close relationship between the spiritual dimension and socio-ecological responsibility. This study makes a significant contribution to the development of hadith-based Islamic environmental jurisprudence. With a methodological and academic approach, this study enriches understanding of Islamic ecological ethics and opens up opportunities for integrating religious values into just and sustainable environmental management.